Exosomal RNF157 mRNA from prostate cancer cells contributes to M2 macrophage polarization through destabilizing HDAC1 - Guan, Han; Mao, Likai; Wang, Jinfeng; Wang, Sheng; Yang, Shuai; Wu, Hongliang; Sun, Wenyan; Chen, Zhijun; Chen, Ming (Frontiers in Oncology, 2022)
Background: Exosomes have been identified to mediate the transmission of RNAs among different cells in tumor microenvironment, thus affecting the progression of different diseases. However, exosomal messenger RNAs (mRNAs) have been rarely explored. RNF157 mRNA has been found to be up-regulated in PCa patients’ exosomes, but the role of exosomal RNF157 mRNA in PCa development remains unclear. Methods: Online databases were utilized for predicting gene expression and binding correlation between different factors. RT-qPCR and western blot assays were respectively done to analyze RNA and protein expressions. Flow cytometry analysis was implemented to analyze M2 polarization. Results: RNF157 expression was high in PCa tissues and cells. M2 polarization of macrophages was enhanced after co-culture with PCa cells or with exosomes released by PCa cells. Upon RNF157 knockdown in PCa cells, the extracted exosomes could not lead to the facilitated M2 polarization. Mechanistically, RNF157 could bind to HDAC1 and contribute to HDAC1 ubiquitination, which led to HDAC1 degradation and resulting in promoting M2 polarization of macrophages. Animal experiments validated that exosomal RNF157 accelerated PCa tumor growth through facilitating macrophage M2 polarization. Conclusion: Exosome-mediated RNF157 mRNA from PCa cells results in M2 macrophage polarization via destabilizing HDAC1, consequently promoting PCa tumor progression.